PRODUKSI LARVA IKAN RAINBOW MERAH PARROT (Glossolepis incisus) DENGAN JUMLAH SUBSTRAT TALI RAFIA YANG BERBEDA - Mustahal Mustahal; Dodi Hermawan; Gugum Gumilar (JURNAL PERIKANAN DAN KELAUTAN, 2014)
Research on larval production of Parrot red rainbow fish Glassolepis incisus has been done by using different numbers of raffia’s rope as substrats for eggs attachment. A raffia’s rope substrats of different plys concentrations namely A 360 plys, B 720 plys, and C 1080 plys were used. The spawning was carried out during 30 days, and larval feeding was given twice a day with frozen Chironomus larvae in ad satiation rate. The results showed that highest spawning frequencies was found in treatment A (360 plys) with 24 times, and then treatment B (720 plys) with 23 times, and treatment C (1080 plys) with 18 times. Highest eggs production were found on treatment A, B and C respectively at 1154 eggs, 892 eggs, and 691 eggs, respectively. Whiles the hatching rate were found that the treatment A = 92 %, treatment B= 85 % and treatment C= 94 %. The Treatment A overall was the best treatment in this experiment.Keyword: Larval, Parrot red rainbow, raffia rope, spawning